COMBINATION OF MORINGA LEAF FLOUR AND PROBIOTICS IN FEED ON THE GROWTH AND SURVIVAL RATE OF TILAPIA JUVENILE - Sumarjan, Nanang Satria; Hilyana, Siti; Azhar, Fariq (Buletin Veteriner Udayana, 2022)
This study aims were to supplement Moringa leaf meal and probiotics into feed. Moringa oliefera leaves are plants that contain high enough protein for growth and contain flavonoids, saponins, and vitamins A, B, C, and E which can trigger endurance, and probiotics can increase the digestibility of food in the fish intestines, so that absorption the nutrients in the feed can be completely absorbed. This study used a completely randomized design consisting of 5 treatments and 3 replications, in order to obtain 12 experimental units. in treatment A (4% moringa leaf meal + 6 ml / kg of feed), B (6% moringa leaf meal + 6 ml / kg of feed), C (8% moringa leaf meal + 6 ml / kg of feed), D (positive control) and E (negative control). Parameters measured were absolute weight growth, absolute length growth, specific weight growth, specific length growth, survival, water quality, and feed conversion. The results showed that the addition of Moringa leaf meal combined with probiotics in the feed had a significant effect on the absolute weight of 4.673 gr, absolute length 2.607 cm, specific weight 2.25%, specific length 1.07%, feed conversion 1.84%, but no significant effect on the survival rate. live tilapia seeds, with the optimum dose to provide the best growth in tilapia seeds is treatment B with a dose of 6% Moringa leaves and 6 ml / kg of probiotic feed.